Design, Fabricate and Test of an Injector Driver for Automotive Direct Injector - Mohd Yunus, Taufiqurrahman (Universiti Teknologi Petronas, 2009)
The objective of this project is to design and test a suitable driver circuit to meet current control objectives. Injector drivers for automotive engines require peakand- hold current control for operation. For this project, the designed circuits need to be tested and compared to an injector driver that is available in the market. Implementation of the driver circuit will be done on PCB using an injector driver chip, PCB maker and schematic capture software. At the end of this project, the fabricated circuit will be tested with an actual automotive injector. Analog electronics and microelectronics knowledge will be applied for designing the circuit and to analyze the acquired data. As a conclusion, this project is to design, fabricate and test an injector driver that can meet current control objectives: peak-and-hold current.